Evaluating Effects of Travel-resonance Method with Color Soy Source and Clear Water on Substance using Fractal Dimension Analysis of Awareness Outward-form - Jang, Kyung T.; Lee, Min H.; Kim, Jeong L. (International Journal of Membrane Science and Technology, 2023)
Soy source has a useful effect on the human body and is the important ingredients in various foods and is an important factor of food engineer that tastes food ingredients. The forming model of the soy source was configured asymmetrical on the fractal surface and mixed with water using travel-resonance method to change a certain amount of viscosity into the shape of the surface. Travel mutational-status technology is structured the resonance status for rainbow dot pattern of the glitter awareness rate (GAR) and inequality awareness rate (IAR) on soy source travel awareness outward-form. Awareness rate condition by soy source travel awareness outward-form is structured with the circulate resonance system. Rainbow dot pattern of the happen mutational-status is to check up to structure of soy source travel value with travel layer location by the circulate-down structure. Concept of awareness rate is check up the reference of glitter rate and inequality rate for mutational-status signal by soy source travel resonance outward-form. Happen mutational-status of the GAR-IAR is presented position value of maximum-minimum on soy source travel-resonance outward-form. Far mutational-status of the Tr-aof-FA-?MAX-MIN presented the travel value with 14.67±7.32 units. Convenient mutational-status of Tr-aof-CO-?MAX-MIN presented the travel value with 4.48±0.46 units. Flank mutational-status of the Tr-aof-FL-?MAX-MIN presented the travel value with 1.29±0.32 units. Vicinage mutational-status of the Tr-aof-VI-?MAX-MIN presented the travel value with 0.23±0.07 units. Circulate resonance will be to inquire into at the ability of soy source travel-resonance outward-form for the restrain degree awareness rate on the GAR-IAR that is stick-out the happen glitter and inequality outward-form by the awareness rate system. Awareness outward-form LED will be to inquire into of outward-form by the inequality signal and to figure a travel data of circulate resonance rate by the circulate awareness system. due to the effect of image resolution.